Yield, Capsaicin Content and Peroxidase Enzyme Activity of Four Chili Cultivars on Three Environments - Mahya Nur Rohmah; Suyadi Mitrowihardjo; Rudi Hari Murti (Jurnal Ilmu Pertanian, 2016)
The experiment aimed to determine the effect of different environment (altitude and drought stress) on the growth, yield per plants, capsaisin levels, and peroxidase activities of four chili cultivars. Capsicum annuum (‘Lado’ and ‘Gada’) and Capsicum frutescens (‘Pelita’ and ‘Sona’) were grown with standard cultivation in medium land (± 700 m asl, Kaliurang) and low land (112 m asl, Bulaksumur) in two environments i.e. standard cultivation and drought treatment. The cultivars were arranged in Complete Randomize Design with four replications in each environment. The data were analyzed using analysis of variance with orthogonal contrast model, while the GGE biplot was applied for identification of stability. The result showed significant interaction between environment and cultivar on plant height, fruit’s weight per plant and the contents of capsaicin. Medium land of Kaliurang had suitable environment for chili cultivation of four cultivars and the high capsaicin content of C. frutescens. ‘Gada’ was significantly higher than other cultivars for fruit weight per plant in all planting conditions, while ‘Sona’ had the highest capsaicin content and was stable in all environments. Drought stress increased capsaicin content in low capsaicin content variety, in contrast to high capsaicin content cultivar. Peroxidase enzyme activity of C. frutescens was significantly higher than C. annuum, while C. annuum cultivars also shown significantly different in peroxidase activity.